2012
DOI: 10.1134/s1061934811120057
|View full text |Cite
|
Sign up to set email alerts
|

Determination of benzoate, sorbate, citrate and orthophosphate ions in beverage samples using two-dimensional isotachophoretic method

Abstract: A two dimensional capillary isotachophoretic method (cITP⎯cITP) using electrolyte system consisting of leading electrolytes (LE1): [10 mM HCl + β alanine (pH 3.9) + 0.1% hydroxyethylcellulose (HEC)] and (LE2): [10 mM HCl + aminocaproic acid (pH 5.00) + 0.1% HEC], and 5 mM caproic acid as terminating electrolyte (TE) was studied. Two methods of detection, conductometric and UV Vis, were applied to the determination of selected food preservatives and additives. Practical applicability was demon strated by simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…In general, these additives can be obtained from nature or manufactured by the chemical industry. The main food additives analyzed by CE in the period covered by this review (2013–2015) were sweeteners , preservatives , and colorants .…”
Section: Food Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these additives can be obtained from nature or manufactured by the chemical industry. The main food additives analyzed by CE in the period covered by this review (2013–2015) were sweeteners , preservatives , and colorants .…”
Section: Food Additivesmentioning
confidence: 99%
“…The developed method was applied to real food samples of juice, two soft drinks, two soy sauces, and a wine sample. Another strategy applied to increase sensitivity for preservatives detection was a two dimensional isotachophoretic cITP‐cITP method . Preservatives were detected by two methods of detection, namely conductometric and UV‐Vis.…”
Section: Food Additivesmentioning
confidence: 99%
“…In a similar way, orthophosphates, pyrophosphates, tripolyphosphates, and nitrites were determined in food samples with LODs about 0.15 mg/L (LE: 10 mM HCl, glycine, 0.02% HEC, pH 3.0; TE: 10 mM phosphoric acid). Jastrzębska et al reported a 2D ITP method for the determination of benzoate, sorbate, citrate, and orthophosphate in beverage samples. By using different electrolyte systems in the preseparation and analytical capillary, LODs from 0.85 to 3.1 mg/L and LOQs from 2.8 to 10 mg/L were obtained using conductivity and UV detection (LE1: 10 mM HCl, β‐alanine, 0.1% HEC, pH 3.9; LE2: 10 mM HCl, aminocaproic acid, 0.1% HEC, pH 5.00; TE: 5 mM caproic acid).…”
Section: Applicationsmentioning
confidence: 99%